2021
DOI: 10.3897/neobiota.67.58147
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs of biological invasions in Asia

Abstract: Invasive species have caused severe impacts on biodiversity and human society. Although the estimation of environmental impacts caused by invasive species has increased in recent years, economic losses associated with biological invasions are only sporadically estimated in space and time. In this study, we synthesized the losses incurred by invasions in Asia, based on the most comprehensive database of economic costs of invasive species worldwide, including 560 cost records for 88 invasive species in 22 countr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Most costs stemmed from direct damage rather than management spending and principally impacted the agriculture sector. This dominance of damage-related costs over management aligns with trends in other geographic regions worldwide (Crystal-Ornelas et al 2021;Haubrock et al 2021a;Heringer et al 2021;Liu et al 2021). Invasion impacts in the UK were largely driven by animals, which were both the most studied and costliest taxa.…”
Section: Question 1: Invasion Costs Distributions Through Space and Sectorssupporting
confidence: 69%
“…Most costs stemmed from direct damage rather than management spending and principally impacted the agriculture sector. This dominance of damage-related costs over management aligns with trends in other geographic regions worldwide (Crystal-Ornelas et al 2021;Haubrock et al 2021a;Heringer et al 2021;Liu et al 2021). Invasion impacts in the UK were largely driven by animals, which were both the most studied and costliest taxa.…”
Section: Question 1: Invasion Costs Distributions Through Space and Sectorssupporting
confidence: 69%
“…However, InvaCost only reported cost data for 35 species, suggesting a huge underestimation of invasion costs in Mexico -since costs are available for only 10% of known IAS. This proportion is similar to that reported in other studies, which have found that less than 10% of invaders have reported costs: Germany , France (Renault et al 2021), the United Kingdom, (Cuthbert et al 2021b), Asia (Liu et al 2021), Argentina (Duboscq-Carra et al 2021 or Australia (Bradshaw et al 2021). Even if one cannot conclude that actual costs should be ten times higher, the very high overall economic costs we found for only 10% of IAS in Mexico hints at a real, total cost that is staggering.…”
Section: Discussionsupporting
confidence: 89%
“…Compared to other regions, Central and South America have higher accumulated costs than Africa (USD 18.2 billion; Diagne et al 2021b) and a similar cost to that found in Europe when we used the same inclusion criteria, considering low reliability or potential costs (USD 140.2 billion; ). However, Central and South America have lower costs than North America and Asia (USD 1.26 trillion and USD 432.6 billion, respectively; Crystal-Ornelas et al 2021;Liu et al 2021). These differences were not entirely surprising considering the lower number of invasive alien species in Central and South America compared with North America (van Kleunen et al 2015;Pyšek et al 2019), as well as the research deficit in invasion biology in Central and South America (Bellard and Jeschke 2015), which can negatively affect the number of reported costs to the continents.…”
Section: General Patternsmentioning
confidence: 99%